"Sekrety Twin Peaks" Marka Frosta - literackie uzupełnienia serialowej fabuły = The secret history of "Twin Peaks" by Mark Frost - a literary supplement to the film series - Gieba, Kamila (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article concerns the relations between the television series "Twin Peaks", directed by David Lynch and Mark Frost, and the book entitled "The Secret Story of Twin Peaks" written by Mark Frost. The author moved the town from screen to paper, enriching the plot with numerous motifs related to the history of America.
Keywords: "Twin Peaks"; Lynch, David (1946- ); series; dossier; formal mimicry; serial